Patient-reported outcome measures as determinants for the utilization of health care among outpatients with epilepsy: a prognostic cohort study - Stine Primdahl Rasmussen; Liv Marit Valen Schougaard; Niels Henrik Hjøllund; David Høyrup Christiansen (SpringerOpen, 2023)
Abstract Background Patient-reported outcome (PRO) measures can inform clinical decision making and planning of treatment in the health care system. The aim of this study was to examine whether patient-reported health domains influence the use of health care services in outpatients with epilepsy. Methods This was a prognostic cohort study of 2,426 epilepsy outpatients referred to PRO-based follow-up at the Department of Neurology, Aarhus University Hospital, Denmark. Patients filled out a questionnaire covering health literacy areas, self-efficacy, well-being and general health. The main outcome was a record of contact to the epilepsy outpatient clinic, inpatient ward and/or emergency room within 1 year, retrieved from health register data. Associations were analysed by multivariable binomial logistic regression. Results A total of 2,017 patients responded to the questionnaire and 1,961 were included in the final analyses. An outpatient contact was more likely among patients with very low health literacy ('social support'): odds ratio (OR) 1.5 (95% CI: 1.1-2.1), very low and low self-efficacy: OR 1.7 (95% CI: 1.2-2.3) and OR 1.4 (95% CI: 1.0-1.8), low and medium well-being: OR 2.2 (95% CI: 1.6-3.0) and OR 1.4 (95% CI: 1.1-1.9), and patients rating their general health as fair: OR 2.8 (95% CI: 1.7-4.6). Inpatient contact and emergency room contact were associated with the health domains of self-efficacy and general health. Conclusions PRO questionnaire data indicated that patients with low health literacy ("social support"), well-being, self-efficacy and self-rated general health had an increased use of health care services at 1 year.These results suggest that PRO measures may provide useful information in relation to the possibility of proactive efforts and prevention of disease-related issues and to help identify efficiency options regarding resource utilization.